Classifying eating‐related problems among institutionalized people with dementia. Issue 4 (22nd December 2015) - Shinagawa, Shunichiro; Honda, Kazuki; Kashibayashi, Tetsuo; Shigenobu, Kazue; Nakayama, Kazuhiko; Ikeda, Manabu
Abstract : Aims: Various eating‐related problems are commonly observed among people with dementia, and these problems place a huge burden on the caregivers. An appropriate classification of these problems is important in order to understand their underlying mechanisms and to develop a therapeutic approach for managing them. The aim of this study was to develop a possible classification of eating‐related problems and to reveal the background factors affecting each of these problems across various conditions causing dementia. Methods: The participants were 208 institutionalized patients with a diagnosis of dementia. Care staff were asked to report all kinds of eating‐related problems that they observed. After the nurses' responses were analyzed, 24 items relating to eating‐related problems were extracted. A factor analysis of these 24 items was conducted, followed by a logistic regression analysis to investigate the independent variables that most affected each of the eating‐related factors. Results: Four factors were obtained. Factor 1 was overeating, factor 2 was swallowing problems, factor 3 was decrease in appetite, and factor 4 was obsession with food. Each factor was associated with different background variables, including Mini‐Mental State Examination scores, Clinical Dementia Ratings, and neuropsychiatric symptoms. Conclusions: This study suggests that eating‐related problems are common across conditions causing dementia and should be separately considered in order to understand their underlying mechanisms.